Enhanced optical absorption of nanosized TiO2 by composition with zeolite - Fukugaichi, Satoru; Matsue, Naoto (Materials chemistry and physics, 2015)
Enhancement of the photocatalytic activity of TiO2 and its mechanism are important subjects in the field of catalysis. Under the coexistence of TiO2 with a diameter of about 20 nm, we synthesized faujasite X-type zeolite, and the product was made up of the composite of TiO2 and faujasite X-type zeolite. The composite had higher acetaldehyde photocatalytic decomposition activity than a corresponding mixture, and the activity of the composite was higher than that of TiO2 on TiO2 mass basis. The composite had higher UV light absorptivity than the corresponding mixture, and their absorption of UV light was mainly due to TiO2. The increased UV light absorptivity of the composite correlated to its increased acetaldehyde photocatalytic decomposition activity. [Display omitted] •TiO2-zeolite composite was synthesized by using nanosized TiO2.•The composite had higher UV light absorptivity than a corresponding mixture.•The increased absorptivity increased the photocatalytic activity of the composite.